Primavera X: gincana como ação mitigadora de problemáticas ambientais na Praia do Mangal em Tucuruí-PA - ALMEIDA, Samayara Nayara Vieira de (2023)
The constant man-made changes in the environment can result in damage to natural resources, including water bodies. The following impacts generated by the community thus hinder the recovery of nature on its own, needing once again human action, acting in the recovery of devastated and/ or polluted areas. This article deals with the importance of actions aimed at the preservation of water resources. Also, the accomplishment of the national game in favor of the care with the waters, Primavera X. In this action, a large amount of garbage was removed from the study site, known as Mangal Beach, in the municipality of Tucuruí. This project was carried out in partnership with a Pathfinder Club in the municipality and obtained the support of parents and relatives of children and adolescents involved. The Primavera X contributed to involve the youth in a water body recovery activity, fulfilling the main objective of the game.